Evaluating the multiple benefits of a sustainable drainage scheme in Newcastle, UK - O'Donnell, Emily C.; Woodhouse, Richard; Thorne, Colin R. (ICE Publishing, 2017)
Sustainable Drainage Systems (SuDS) and Blue-Green infrastructure (BGI) provide a range of environmental, economic and social benefits in addition to managing water quantity and quality. Recognition of the multifunctionality of SuDS and BGI, and the specific benefits that may accrue to different beneficiaries, may facilitate partnership working towards multifunctional infrastructure that meets the strategic objectives of public and private organisations. We evaluate the multiple benefits of the Killingworth and Longbenton surface water management scheme, a Partnership Project in NE England jointly funded by Northumbrian Water, the Environment Agency and North Tyneside Council. Using CIRIA’s Benefits of SuDS Tool (BeST) and the Blue-Green Cities Multiple Benefits GIS Toolbox, we a) quantify and monetise six key benefits, b) assess two qualitative benefits, c) illustrate the spatial distribution of five non-flood benefits, and d) highlight locations with the greatest opportunity for multi-beneficial intervention. The Killingworth and Longbenton scheme generates; significant flood damage reduction benefits; improves water quality, habitat size, carbon sequestration, attractiveness of the area and property prices (amenity), and; reduces noise pollution. Utilisation of these complementary tools for multiple benefit evaluation shows promise as an aid to facilitate partnership working towards implementation of multifunctional SuDS and BGI.